Clinical, biochemical, and genetic features of four patients with short‐chain enoyl‐CoA hydratase (ECHS1) deficiency. Issue 5 (25th March 2018) - Fitzsimons, Patricia E.; Alston, Charlotte L.; Bonnen, Penelope E.; Hughes, Joanne; Crushell, Ellen; Geraghty, Michael T.; Tetreault, Martine; O'Reilly, Peter; Twomey, Eilish; Sheikh, Yusra; Walsh, Richard; Waterham, Hans R.; et al.
Abstract : Short‐chain enoyl‐CoA hydratase (SCEH or ECHS1) deficiency is a rare inborn error of metabolism caused by biallelic mutations in the gene ECHS1 (OMIM 602292). Clinical presentation includes infantile‐onset severe developmental delay, regression, seizures, elevated lactate, and brain MRI abnormalities consistent with Leigh syndrome (LS). Characteristic abnormal biochemical findings are secondary to dysfunction of valine metabolism. We describe four patients from two consanguineous families (one Pakistani and one Irish Traveler), who presented in infancy with LS. Urine organic acid analysis by GC/MS showed increased levels of erythro ‐2, 3‐dihydroxy‐2‐methylbutyrate and 3‐methylglutaconate (3‐MGC). Increased urine excretion of methacrylyl‐CoA and acryloyl‐CoA related metabolites analyzed by LC‐MS/MS, were suggestive of SCEH deficiency; this was confirmed in patient fibroblasts. Both families were shown to harbor homozygous pathogenic variants in the ECHS1 gene; a c.476A > G (p.Gln159Arg) ECHS1 variant in the Pakistani family and a c.538A > G, p.(Thr180Ala) ECHS1 variant in the Irish Traveler family. The c.538A > G, p.(Thr180Ala) ECHS1 variant was postulated to represent a Canadian founder mutation, but we present SNP genotyping data to support Irish ancestry of this variant with a haplotype common to the previously reported Canadian patients and our Irish Traveler family. The presence of detectable erythro ‐2, 3‐dihydroxy‐2‐methylbutyrate is a nonspecific marker on urine organic acid analysis but this finding, together with increased excretion of 3‐MGC, elevated plasma lactate, and normal acylcarnitine profile in patients with a Leigh‐like presentation should prompt consideration of a diagnosis of SCEH deficiency and genetic analysis of ECHS1 . ECHS1 deficiency can be added to the list of conditions with 3‐MGA.